Reverse Bullying as a Defense Mechanism : Analysis of the Cognitive-Behavioral Cycle in the Transformation from Victim to Bully - Larous, Zouina; Benkherouf, Amina; Bordi, Malika Ben (Journal of Ecohumanism, 2026)
This article aims to analyze the phenomenon of reverse bullying as a complex and maladaptive psychological defense mechanism, whereby an adolescent who was previously a victim of abuse becomes a perpetrator of bullying toward others. The analysis focuses on elucidating the role of this mechanism in expressing repressed anger and feelings of shame, as well as in attempting to regain a sense of lost control. The process of transformation is interpreted through mechanisms such as displaced aggression and compensation. The analysis is further consolidated by deconstructing the cognitive–behavioral cycle through which hostile attribution bias develops in the adolescent, enabling the justification of aggressive behavior. Verbal aggressive behavior is reinforced by the immediate sensation of power and illusory status, which necessitates an integrated cognitive–behavioral therapeutic approach centered on modifying core beliefs related to power and aggression.